GEOCHEMISTRY AND STABLE ISOTOPIC SIGNATURES, INCLUDING CHLORINE AND BROMINE ISOTOPES, OF THE DEEP GROUNDWATERS OF THE SIBERIAN PLATFORM, RUSSIA - Shouakar-Stash O.; Frape S.K.; Drimmie R.J.; Alexeev S.V.; Alexeeva L.P. (My University, 2007)
The chemical composition and the isotopic characteristics of formation waters from the Siberian Platform are presented. The study involved samples of formation brines from depths ranging from 100 to ~4000 m at five different sites covering a large area of the Siberian Platform. Four water types were identified. The two main water types that were found are: (1) Ca-Cl brines that are believed to be the residual of an evaporated paleoseawater; and (2) Na-Cl brines that are derived mainly from halite dissolution. The origin of a third group of highly saline samples was not determined. However, the chemical and isotopic characteristics of this group of samples suggest that they were produced by various complex scenarios such as metamorphism, water-rock interaction, permafrost freezing and mixing. The last group of samples represents fresh and brackish waters across the area. A wide range for the natural variation of Br stable isotopes (between -0.80‰ and +3.35‰) was found. The δ81Br results obtained during this study indicate that Br stable isotopes can have large natural variations and that different evolutionary processes affecting water chemistry may cause significant fractionation. © 2006 Elsevier Ltd. All rights reserved.